Optimización del proceso de trituración-molienda, mediante la reducción de la malla granulométrica en la planta de beneficio “Playitas”, Sector El Salado, Cantón Portovelo, Provincia de El Oro. - Armijos Camacho, Pablo David (2024)
The present Curriculum Integration Research work entitled “Optimization of the Crushing-Grinding Process, Through the Reduction of the Granulometric Mesh in the “Playitas” Beneficiation Plant, El Salado Sector, Portovelo Canton, Province of El Oro”, was carried out in based on a qualitative and quantitative investigation, through a field phase, where samples were collected in the tent-type stock of the plant, which stores the All-One from the “O Nivel” mining area, located 20 km in the canton Zaruma. In this same phase, the technical-productive characteristics of the comminution equipment were detailed through a field inspection. In the laboratory and office phase, the respective analyzes were developed to characterize the mineral and the respective compilation and writing of the results obtained was carried out. The “Playitas” Beneficiation Plant processes 300 tons per day in the most common line of work, recovering gold concentrate from the ore extracted from the mine, which has been subjected to a crushing, grinding and flotation process. The material it processes is an andesite, which contains minerals of: Quartz, Qtz (SiO2); Chlorite, Chl ((Mg,Fe)3(Si,Al)4O10 (OH)2·(Mg,Fe)3(OH)6); Kaolinite, Kln (Al2Si2O5(OH)4) in small percentages; Pyrite, Py (FeS2); Chalcopyrite, Ccp (CuFeS2); Galena, Gn (PbS); Sphalerite, Sp (ZnS) and encapsulated gold (Au) visible at 18 μm. The rock is compact, has a density of 2.86 gr/cm3 and is classified as a “high to exceptional resistance” and very abrasive rock. The equipment that is described within the processing and concentration of minerals; They are: a 210-ton bulk hopper with bars separated by ≈40 cm located in the upper part of it, with the purpose of functioning with a first stage of material separation. At the bottom of the hopper, there is a reciprocating feeder connected to a plate vibrating screen; which fulfills the function of feeding the primary jaw crusher, 500 x 600 mm (Bxb). Subsequently, there is a vibrating screen 5.6 m2 with a ¾-inch mesh, in which the material that meets the required size is ground and the retentate is transferred to secondary crushing using a 200 x 1200 mm (axD) Symons-type conical crusher. The 2.1 x 3.6 m (DxL) ball mill reduces the material to plus or minus #200 mesh; and, the grinding medium, made up of forged steel balls (4” – 3” – 2”), in a quantity of 17 tons. Using the Gates Gaudin Schuhmann methodology, the granulometry of the product of the jaw crusher, cone crusher and screening efficiency were evaluated, resulting in a circulating load of 118% (high for a primary crushing stage) and an energy consumption monthly of 13020 kW ($1171.8). The proposed circuit obtained a higher circulating load, but 5 the value is within the range for a closed circuit in the secondary crushing stage, resulting in an energy consumption of 12448.5 kW ($1120.36), according to the light form (05/15/2024) provided by the plant. In order to improve grinding, the calculation of tonnage of steel balls and optimal ball size for the mill of the benefit plant was carried out, resulting in a total of 18.6 Ton with a maximum size of 5 inches up to a size minimum of 1 inch, giving a cost of $15,533.29. 4 grinding time tests were carried out to provide a solution to the main unknown of the project, which is based on knowing at what granulometry the percentage of gold recovery is increased (currently the plant handles 75% recovery). In the test of sample M4 with a time of 1 hour and 45 minutes, an optimal size of 54 microns was determined by applying Gates Gaudin Schuhmman and 90% was recovered through a flotation test using the same reagents used in the manufacturing plant. benefit on a smaller scale. Giving an increase of 1.16 grams in the concentrate grade, which, in economic terms, would bring in $ 36494.2 per month. Keywords: Granulometry, crushing, circulating load, grinding, grinding time, recovery.